2019
DOI: 10.1016/j.cmi.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility testing and species identification of Nocardia isolates: a retrospective analysis of data from a French expert laboratory, 2010–2015

Abstract: In this first epidemiological study of Nocardia isolated from human samples in France, N. farcinica was the species most frequently identified and its prevalence increased over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
89
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 24 publications
10
89
0
1
Order By: Relevance
“…N. farcinica IFM 10152 is a reference strain whose genome has previously been sequenced (GenBank accession number AP006618) (23). Ten N. farcinica clinical isolates were selected from the collection of the Observatoire Français des Nocardioses (see Table S2 in the supplemental material) (5).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…N. farcinica IFM 10152 is a reference strain whose genome has previously been sequenced (GenBank accession number AP006618) (23). Ten N. farcinica clinical isolates were selected from the collection of the Observatoire Français des Nocardioses (see Table S2 in the supplemental material) (5).…”
Section: Methodsmentioning
confidence: 99%
“…imipenem (overall frequency of 23 to 67%) (5)(6)(7)(8)(9) precludes the use of any ␤-lactam (coresistance frequency of 23%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MS1-3t and AS4-2 were isolated in Japan respectively from a moat sediment and from sludge obtained from a sewage treatment plant. To date, only nine clinical isolates of N. takedensis have been reported in human [2][3][4][5][6][7][13][14][15]. The main clinical and microbiological features of N. takedensis isolates are summarized in the Table 1.…”
Section: Open Accessmentioning
confidence: 99%
“…Moreover, Brown-Elliott et al, have previously suggested that Nocardia brasiliensis, a species that is phylogenetically closely related to N. takedensis, is predominantly isolated in tropical or subtropical region [16]. Recently, Lebeaux et al, showed a higher density of Nocardia isolates in the South of France and overseas territories than in other French areas, suggesting that environmental conditions may also increase the spread of Nocardia sp [14]. To date, data found in the literature concerning the potential impact of the climatic conditions on soil and on N. takedensis spreading are scarce and further studies will be necessary to assess this challenging hypothesis.…”
Section: Open Accessmentioning
confidence: 99%